The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/caim.12205
|View full text |Cite
|
Sign up to set email alerts
|

Individual Creativity during the Ideation Phase of Product Innovation: An Interactional Perspective

Abstract: Although there is increasing acknowledgement that employees' creative ideas are fundamental for product innovation, and many companies use cross‐functional teams to increase employee creativity, there has been little empirical testing of how individual personality and group context interactively affect individual creativity. The purpose of this study is threefold: to examine the relationship between personality and individual creativity; to assess how this relationship interacts with group diversity; and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 69 publications
(111 reference statements)
3
43
3
2
Order By: Relevance
“…However, at present, scholars have different opinions on the influence of neuroticism on creativity. For instance, some studies found a negative association between neuroticism and creativity ( Guo et al, 2017 ). In contrast, others have found that self-rated creativity is positively related to neuroticism ( Batey et al, 2010 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present, scholars have different opinions on the influence of neuroticism on creativity. For instance, some studies found a negative association between neuroticism and creativity ( Guo et al, 2017 ). In contrast, others have found that self-rated creativity is positively related to neuroticism ( Batey et al, 2010 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In addition, Srivastava and Ketter (2010) , through meta-analysis, found that neurotic creative business professionals are more creative than non-neurotic business professionals. Some scholars claim that emotionally stable individuals with low neuroticism are relatively relaxed and have a positive view of the tasks of themselves and others ( Guo et al, 2017 ). Creativity requires the ability to effectively integrate information and seek a new way of thinking, which can be enhanced by a calm attitude and self-confidence.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The first one is informational diversity which refers to differences in characteristics such as educational background and functional experience and is related to the kind of concrete information each member brings to the team. Social category diversity refers to demographic differences such as gender, age and tenure among the members of the team (Guo, et al, 2017). Informational diversity in teams is less visible and more task-related than social category diversity.…”
Section: Teambuildingmentioning
confidence: 99%
“…Early creativity research focused on personality traits as predictors of creative outcomes. Further work on creativity has continued to examine personality traits, finding significant and positive relationships between the Big‐Five personality factors of openness to experience, extraversion and conscientiousness, and creative output (Cirella, ; Gassmann, ; George & Zhou, ; Guo, Su, & Zhang, ; Perkins, Lean, & Newbery, ; Shalley, ; Sung & Choi, ). On a different track, creativity researchers separately began to focus on cognitive styles to explore the impact on creative behaviour.…”
Section: Introductionmentioning
confidence: 99%